Inundasi Agensia Hayati Corynebacterium Untuk Meningkatkan Hasil Berbagai Varietas Kedelai Di Daerah Endemik Penyakit Karat - Gayuh Prasetyo Budi (Universitas Muhammadiyah Jember, 2023)
The objective of this research was to study response of the growth, yield and the resistance of several soybean varieties to rust diseases. The experimental research was conducted at Dukuhwaluh Village, Kembaran, Banyumas from November 2016 to July 2017. The experiment used a Completely Randomized Design with 2 factors and 3 replications. Factor 1. Soybean Variety, consisted of : (V1) Detam 1, (V2) Detam 3, (V3) Detam 4, (V4) Dena 1, (V5) Dena 2, (V6) Baluran, (V7) Slamet, (V8) Anjasmoro 2. Corynebacterium, consisted of C0 : no applied corynebacterium , C1 : applied corynebacterium 3 times, C2 : applied corynebacterium 6 times. The result showed that Slamet variety and Anjasmoro variety show the better yield than other. Slamet variety and Anjasmoro variety can produce of seed weight : 23.46 g and 21.22 g per plant. All varieties have disease susceptibility that is not significantly different. Giving Corynebacterium 3 times and 6 times on soybean varieties can reduce the intensity of rust disease from 41.18% to 20.14% and 23.77%. The two treatment factors did not show any real interaction with all observed variables